RANCANG BANGUN SISTEM PENGELOLAAN PELATIHAN SOFTSKILL : Pada Pusat Karir Universitas Pembangunan Nasional Veteran Jakarta. - Yussari'uuna Filkhoiroh (2020)
The development of universities nowadays has major responsibility to maximize student's quality in a way to conduct trainings and individual development in aim to increasing knowledge and student's ability to face the factual of work environment, on the other hand it can bound in honour the institute or universities when graduates obtain the satisfactory results. Therefore, a softskill training management system is needed so a research was made on The Design of Management System for the Career Center of the "Veteran" National Development University of Jakarta. The used of system development method is the prototype method. The outcome of this research is a web-based Career Center Management System which is expected to help UPT Kewirausahaan dan Pengembangan Karir in order to provide the information and data processing.